Queue Management, Service Quality and Patient Satisfaction in Hospital Services: A Systematic Literature Review and Bibliometric Analysis - Muhammad Syaifullah Noer (DINASTI RESEARCH, 2026)
This study aims to analyze the development of research related to patient satisfaction in the context of queue management, service quality, and hospital services through a Systematic Literature Review (SLR) and bibliometric analysis approach. The study utilized the Scopus database with the keywords waiting time, service quality, patient satisfaction, and hospital. In this study, the concept of queue management was represented through the variable waiting time because the term is more widely used in healthcare service research to describe the effectiveness of queue systems and the efficiency of patient flow. The initial search process identified 1,023 articles, which were subsequently screened using the PRISMA framework, resulting in 105 relevant articles for further analysis. Bibliometric analysis was conducted using VOSviewer software to map keyword relationships, publication distribution, collaboration patterns, and research trends. The findings indicate that research on waiting time, service quality, and patient satisfaction has continued to develop significantly and remains highly relevant in healthcare service research. The results also reveal that waiting time has a strong relationship with patient satisfaction and service quality, indicating that effective queue management plays an important role in improving patient experience and hospital service efficiency. In addition, service quality dimensions such as healthcare communication, service responsiveness, empathy, and hospital facilities were identified as dominant factors influencing patient satisfaction. The bibliometric analysis further demonstrates that research on this topic has developed globally, with major publication contributions from China, the United Kingdom, the United States, India, and Indonesia. This study also found that the integration of healthcare technologies such as Queue Management Systems (QMS), Artificial Intelligence (AI), telemedicine, and smart healthcare systems still offers substantial opportunities for future development in improving hospital service quality and patient experience.